Positive solutions for singular systems of multi‐point boundary value problems. (21st June 2012) - Henderson, Johnny; Luca, Rodica
<x xml:space="preserve">Abstract</x> We study the existence of positive solutions for systems of singular nonlinear second‐order ordinary differential equations subject to multi‐point boundary conditions. Copyright © 2012 John Wiley & Sons, Ltd.